Irritable Bowel Syndrome in Terms of Changes in the Microbiota - Vladimir T. Ivashkin; Oxana Yu. Zolnikova (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim: to review available data confirming the pathogenetic role of the intestinal microbiota in the formation of irritable bowel syndrome (IBS).Key findings. Changes in the intestinal biotope cause the development of visceral hypersensitivity and impaired intestinal motor activity, as well as neuroimmune transmission. This article discusses the main aspects of the biological properties of probiotic bacteria in terms of their action within the “brain — intestine — microbiota” chain. The results of experimental and clinical studies elucidating the mechanisms of action of probiotic cultures have been generalized. The understanding of these mechanisms allows practitioners to make informed decisions in prescribing probiotics to IBS patients. Key concepts concerning fecal microbiota transplantation, as well as the prospects and difficulties of implementing this approach are considered.Conclusions. The term “microbiota — intestine — brain” clearly demonstrates the correlation between the main functional components of IBS. Meta-analyses and systematic reviews confirm the efficacy of probiotics in IBS. However, further research into probiotic therapy options is needed to identify specific bacterial strains with proven clinical efficacy. The fecal microbiota transplantation method also requires further research, since many issues associated with this approach remain unclear.